miRNA Expression Profile after Status Epilepticus and Hippocampal Neuroprotection by Targeting miR-132 - Jimenez-Mateos, Eva M. (American Society for Investigative Pathology, 2011)
When an otherwise harmful insult to the brain is preceded by a brief, noninjurious stimulus, the brain becomes tolerant, and the resulting damage is reduced. Epileptic tolerance develops when brief seizures precede an episode of prolonged seizures (status epilepticus). MicroRNAs (miRNAs) are small, noncoding RNAs that function as post-transcriptional regulators of gene expression. We investigated how prior seizure preconditioning affects the miRNA response to status epilepticus evoked by intra-amygdalar kainic acid in mice. The miRNA was extracted from the ipsilateral CA3 subfield 24 hours after focal-onset status epilepticus in animals that had previously received either seizure preconditioning (tolerance) or no preconditioning (injury), and mature miRNA levels were measured using TaqMan low-density arrays. Expression of 21 miRNAs was increased, relative to control, after status epilepticus alone, and expression of 12 miRNAs was decreased. Increased miR-132 levels were matched with increased binding to Argonaute-2, a constituent of the RNA-induced silencing complex. In tolerant animals, expression responses of >40% of the injury-group-detected miRNAs differed, being either unchanged relative to control or down-regulated, and this included miR-132. In vivo microinjection of locked nucleic acid-modified oligonucleotides (antagomirs) against miR-132 depleted hippocampal miR-132 levels and reduced seizure-induced neuronal death. Thus, our data strongly suggest that miRNAs are important regulators of seizure-induced neuronal death.